Practice, Power and Place: Southern British Perspectives on the Agency of Early Medieval Rulers' Residences. Issue 1 (3rd July 2021) - Thomas, Gabor; Scull, Christopher
Abstract : This paper advances understanding of rulership over the fifth to the ninth centuries AD, drawing upon a category of elite settlement from southern Britain known as the great hall complex. Guided by a practice-based conceptual framework, we connect these sites with the embodied regimens, rituals, habits, and activities through which rulership was constituted in the early medieval world. Harnessing recent expanded datasets, we generate insights in three key areas. First, by documenting the significant and sustained antecedent occupation attested at great hall sites, we reveal how rulers exploited the complex multiple pasts of these places to advance symbolic and worldly agendas. Second, we reframe understanding of hall construction as a strategy of elite legitimation by focusing attention on the agency of the skilled practitioners who created these innovative architectural statements and, in doing so, recognize these hitherto neglected specialists as 'crafters' of rulership. Third, we use proxies from recently investigated great hall complexes to reconstruct the networks of dependency and interaction which enmeshed these centres. A concluding comparative discussion of southern Britain and Scandinavia contributes shared perspectives on rulers' residences as a prime arena for the orchestration and creative renewal of early medieval sovereignty.